تذرير السوائل باستخدام قرص دوار مع هزاز - تقلا جوني; قدسية سامي; حسون ثراء (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن هذا البحث إيجاد طريقة لتذرير السوائل بواسطة قرص دوار +هزاز من أجل تأمين قطرات من السائل بأقطار صغيرة جدا /عدة ميكرونات/ متقاربة من بعضها البعض ومتجانسة. الهدف من هذه العملية تذرير السوائل بدون وجود مركبات فريونية المستخدمة عادة في البخاخات، والاستفادة منها أيضا في الاستخدامات الطبية والكيميائية والصناعية،مما يساعد في تخفيض الكلفة الاقتصادية من جهة ، والحفاظ على البيئة من جهة أخرى. The purpose of this research is to find a technique for atomization of liquids by a rotating disk and vibrator to produce tiny drizzles of liquids, this device should produce the same size of drizzles with the same diameter and should be about few microns, so as to be able to spray liquids without Freon compounds which are usually used in sprayers. This way of atomization can be put into chemical medical and industrial use and is both cost effective and envirenment friendly.